2023
DOI: 10.1002/mc.23590
|View full text |Cite
|
Sign up to set email alerts
|

Baohuoside I inhibits resistance to cisplatin in ovarian cancer cells by suppressing autophagy via downregulating HIF‐1α/ATG5 axis

Abstract: Since chemotherapy's therapeutic impact is diminished by drug resistance, treating ovarian cancer is notably challenging. Thereafter, it is critical to develop cutting‐edge approaches to treating ovarian cancer. Baohuoside I (derived from Herba Epimedii) is reported to have antitumor properties in various malignancies. It is unknown, however, what role Baohuoside I plays in cisplatin (DDP)‐resistant ovarian cancer cells. 3‐(4,5)‐dimethylthiahiazo (‐z‐y1)‐3,5‐di‐phenytetrazoliumromide (MTT), colony formation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…This finding is consistent with the previous reports that BHS synergizes chemotherapy in multiple malignancies. For example, BHS inhibited cisplatin resistance in ovarian cancer by suppressing autophagy via downregulating the HIF‐1α/ATG5 axis (Zhou et al., 2023 ). BHS also potentiated paclitaxel chemotherapy in human melanoma by inducing apoptosis via inhibiting the TLR4 pathway (Wu et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is consistent with the previous reports that BHS synergizes chemotherapy in multiple malignancies. For example, BHS inhibited cisplatin resistance in ovarian cancer by suppressing autophagy via downregulating the HIF‐1α/ATG5 axis (Zhou et al., 2023 ). BHS also potentiated paclitaxel chemotherapy in human melanoma by inducing apoptosis via inhibiting the TLR4 pathway (Wu et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that BHS inhibits breast cancer growth and metastasis by suppressing TAM/CXCL1‐induced self‐renewal of CSCs (Wang et al., 2020 ). In addition to these direct cancer inhibition effects, recent studies revealed that BHS has the potential to act as an adjuvant agent to chemosensitise malignancies with other cytotoxic drugs (Wu et al., 2012 ; Zhou et al., 2023 ). For example, BHS synergistically interacted with cisplatin to chemosensitise ovarian cancer by suppressing autophagy via downregulating the HIF‐1α/ATG5 axis (Zhou et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy is a necessary cellular process for the physiological cellular turnover. Thereby, dysregulation in this process is one of the main cause of the tumorgenesis, progression of multiple malignancies and resistance to cisplatin treatment including ovarian cancer [ [198] , [199] , [200] ].…”
Section: Circrnas Affect Ddp Resistance In Ovarian Cancer By Targetin...mentioning
confidence: 99%
“…The risk factors for ovarian cancer include genetic and environmental factors, such as geographic differences and family history [ 2 , 3 ]. Chemotherapy is a commonly used therapeutic approach to ovarian cancer, but its efficiency is limited by drug resistance [ 4 ]. Early diagnosis is the most effective method to prevent advanced ovarian cancer [ 1 ].…”
Section: Introductionmentioning
confidence: 99%